Overview of the Level of Knowledge and Attitudes about Abortion in Students of the S1 Nursing Study Program, Faculty of Medicine Mulawarman University - Shinta Dwie Lestari; Siti Ramadhani; Anik Puji Rahayu; Pratiwi Christa Simarmata (Fakultas Kedokteran, Universitas Mulawarman, 2025)
Background: Abortion is one of the problems that often occurs in adolescents and young adults, including university students, due to a lack of knowledge about reproductive health and the influence of the social environment. Purpose: Students as an educated group are expected to have a good understanding of this issue. Methods: This study is quantitative with a descriptive research design. The sample of this study consists of 52 respondents, specifically S1 Nursing Students. Faculty of Medicine, Mulawarman University (total sampling). The measuring tool used was a questionnaire with 15 closed-ended questions. Data analysis in univariate. Results: It shows that majority of respondents are 18 years old, as many as 31 (59.6%), the gender characteristics of the majority of women are 41 or (78.8%), the characteristics of the majority of fathers' education, namely high school, as many as 30 or 57.7%, and the majority of mothers' education, namely, high school, as many as 20 (38.5%). In the results of this study, it was found that the level of knowledge about abortion in s1 nursing students of the Faculty of Medicine, Mulawarman University was highly knowledgeable, namely 40 respondents (78.9%), and attitudes about abortion in S1 nursing Students of the Faculty of Medicine, Mulawarman University had a good attitude, namely 43 respondents (82.8%). Conclusions: The level of knowledge and attitude about abortion in S1 nursing Students of the Faculty of Medicine, Mulawarman University have high knowledge and a good attitude